1988
DOI: 10.1128/mcb.8.6.2668
|View full text |Cite
|
Sign up to set email alerts
|

L-myc cooperates with ras to transform primary rat embryo fibroblasts.

Abstract: Recent molecular analysis has revealed that L-myc has several domains of extremely conserved anino acid sequence homology with c-myc and N-myc, suggesting similarity of function. We tested the biologic activity of L-myc by using an expression vector containing a cDNA clone coding for the major open reading frame in the 3.9-kilobase mRNA of L-myc under the control of a strong promoter (Moloney long terminal repeat) and found that L-myc complemented an activated ras gene in transforming primary rat embryo fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 32 publications
4
69
0
Order By: Relevance
“…In contrast, L-myc is only 1 ± 10% as e ective (Birrer, 1988). It was originally proposed that this was due to L-myc possessing a weaker TAD than either cmyc or N-myc (Barrett et al, 1992).…”
Section: Erential E Ects Of Myc Proteins On Dna Binding Transcripmentioning
confidence: 98%
“…In contrast, L-myc is only 1 ± 10% as e ective (Birrer, 1988). It was originally proposed that this was due to L-myc possessing a weaker TAD than either cmyc or N-myc (Barrett et al, 1992).…”
Section: Erential E Ects Of Myc Proteins On Dna Binding Transcripmentioning
confidence: 98%
“…22 Furthermore, under certain conditions, L-myc can promote the growth of transformed cells as well as, or better than, c-myc. 17 Together, these observations suggest that, while some functions of myc proteins are overlapping and redundant, others are unique.…”
Section: Introductionmentioning
confidence: 96%
“…14 ± 16 This has suggested that the three myc proteins serve different functions, a notion underscored by the finding that L-myc is only 1 ± 10% as efficient as c-myc or N-myc in transforming primary fibroblasts and that it contains a comparatively weak transactivation domain. 17,18 Other evidence for functional differences among the three myc proteins stems from the different phenotypes of c-myc, Nmyc, and L-myc knockout mice, 16,19,20 the association of each myc gene with a distinctive spectrum of naturally occurring neoplasms, 21 and their differential abilities to alter the sensitivity of cells to chemotherapeutic drugs. 22 In contrast, each myc protein is equally effective at enhancing the apoptotic response of hematopoietic cells to growth factor withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…The c-Myc protein exhibits sequence-speci®c DNA binding when dimerized with its partner Max, and DNA binding is mediated through the basic region, which recognizes the core sequence CACGTG (Berberich et al, 1992;Blackwell et al, 1993;Blackwood and Eisenman, 1991;, but exhibits somewhat higher a nity for the more extended sequence ACCACGTGGT (Berberich et al, 1992;Blackwell et al, 1993;Halazonetis and Kandil, 1991). There are three closely related Myc family proteins (c-Myc, N-Myc and L-Myc), each with documented oncogenic potential (Birrer et al, 1988;Schwab et al, 1985;Yancopoulos et al, 1985) and similar DNA binding properties (Mukherjee et al, 1992). For simplicity, we will use the term Myc to refer to all three proteins, but delineate any distinct activities where they apply.…”
mentioning
confidence: 99%